Association of childhood abuse with behavioral weight‐loss outcomes: Examining the mediating effect of binge eating severity. Issue 1 (21st December 2021) - Emery Tavernier, Rebecca L.; Mason, Susan M.; Levy, Rona L.; Seburg, Elisabeth M.; Sherwood, Nancy E.
Abstract: Objective: The study aims were to (1) document the relationship between a history of childhood abuse and weight change during behavioral obesity treatment and (2) estimate the indirect effect of childhood abuse on weight change through binge eating severity. Methods: Participants ( n = 431) were enrolled in a behavioral weight‐loss intervention. Childhood physical and emotional abuse history and current binge eating severity were self‐reported. Percent weight loss at 6 months was calculated using measured weight. Adjusted mediation models examined whether there was an indirect effect of childhood physical and emotional abuse on 6‐month percent weight loss that operated through binge eating severity. Results: After covariate adjustment, childhood physical abuse, but not emotional abuse, predicted a lower percent weight loss ( B = −1.78%; 95% CI: −3.10% to −0.47%). Although childhood physical and emotional abuse were positively related to baseline binge eating severity, binge eating severity did not mediate the associations between either childhood abuse type and percent weight loss. Conclusions: Individuals with a childhood physical abuse history had a lower percent weight loss than those without such histories during behavioral obesity treatment. This effect was not explained by binge eating severity. Individuals with a history of childhood abuse may benefit from trauma‐informed obesity care.